Correction: Wang et al. Effectiveness in Mitigating Forest Fire Ignition Sources: A Statistical Study Based on Fire Occurrence Data in China. Fire 2022, 5, 215 - Haihui Wang; Bangxin Jin; Kaixuan Zhang; Shamima Aktar; Zhilong Song (Fire, 2023)
In the original publication [...]